CTA Annual Report 2017 - A year in review: Moving to next-generation farming - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2018)
At CTA, we leverage the power of knowledge, innovation and technology, particularly information and communication technologies (ICTs), to make a difference to the lives of rural people across Africa, the Caribbean and the Pacific.We have stepped up our efforts to encourage youth entrepreneurship, support climate-smart agriculture, and promote digitalisation to improve the productivity and resilience of agricultural value chains. CTA’s renowned publishing programme now has a far stronger online presence than in the past, providing ready access to much needed technical knowledge for millions of readers.